Character Education Perspective KH. Hasyim Asy'ari’s and its Relevance in the Digital Age - Fadli, Muhammad Rijal; Kissiya, Efilina (Swarnadwipa, 2024)
Character education, in general, is still at the level of memorizing or introducing values but has not yet reached the level of appreciation of values, let alone to the level of making these values individual commitments in life in today's digital era. The purpose of this study is to analyze the concept of character education from the perspective of KH. Hasyim Asy'ari and its relevance in the digital era. The method used is literature study, data analysis uses content analysis, and descriptive studies related to character education according to KH. Hasyim Asy'ari uses primary and secondary data sources obtained from previous studies in the form of books or journals. The results of the study explain that character education according to KH. Hasyim Asy'ari who focuses on Islamic education is to make a complete human being who has a balance between strong faith and knowledge, high scientific competence, is mentally strong, and has good social mental toughness in the family, school, and community environment. This concept is certainly relevant to be internalized in today's digital era to become human beings who are adaptive to the times and still maintain noble character values.